Orange world and other stories ebook - Russell, Karen (2019)
From the Pulitzer Finalist and universally beloved author of the New York Times best sellers Swamplandia! and Vampires in the Lemon Grove , a stunning new collection of short fiction that showcases Karen Russell’s extraordinary, irresistible gifts of language and imagination.   Karen Russell’s comedic genius and mesmerizing talent for creating outlandish predicaments that uncannily mirror our inner in lives is on full display in these eight exuberant, arrestingly vivid, unforgettable stories.  In“Bog Girl”, a revelatory story about first love, a young man falls in love with a two thousand year old girl that he’s extracted from a mass of peat in a Northern European bog.  In “The Prospectors,” two opportunistic young women fleeing the depression strike out for new territory, and find themselves fighting for their lives.  In the brilliant, hilarious title story, a new mother desperate to ensure her infant’s safety strikes a diabolical deal, agreeing to breastfeed the devil in exchange for his protection. The landscape in which these stories unfold is a feral, slippery, purgatorial space, bracketed by the void—yet within it Russell captures the exquisite beauty and tenderness of ordinary life. Orange World is a miracle of storytelling from a true modern master.